PERSPECTIVES OF CLINICAL EXPERTS ON THE CURRENT USAGE PATTERNS AND THE PREFERENCE OF VILDAGLIPTIN IN THE TREATMENT OF TYPE 2 DIABETES - S, Manjula; KUMAR M, KRISHNA (Innovare Journal of Medical Sciences, 2024)
Objective: Although the efficacy and safety of vildagliptin have been proven in randomized clinical trials, data regarding the improved and up-to-date understanding on the management of Type 2 diabetes mellitus from the context of Indian diabetic patients, are scarce. This study was conducted to assess the opinions of clinical experts on the current usage patterns of vildagliptin in the management of Type 2 diabetes among Indian patients. Methods: A cross-sectional, questionnaire-based study was conducted to collect opinion among physicians in endocrinology across India between June 2022 and December 2022. Convenient sampling method was used. Descriptive statistics were used to summarize the characteristics of the study by employing frequencies and percentages. Results: It was observed that 95 out of 188 clinicians preferred dipeptidyl peptidase-4 (DPP4) inhibitors (DPP4i) and only 35 out of 188 clinicians (18.6%) opted a combination of Metformin and DPP4 inhibitors as the first hypoglycemic agent for newly detected diabetes. In addition, 141 out of 188 (75%) prescribed vildagliptin only as their preferred drug in the class of DPP4 inhibitors. Further, the reason behind such a high-yielding response for vildagliptin among clinicians and their patients, was its weight-neutral property primarily and posing a low risk of adverse effects. Nearly, half of the clinicians reported a 0.6–1% drop in glycosylated hemoglobin (HbA1c) levels in patients within 3 months of vildagliptin use. Conclusion: This study concluded that the majority of the specialists preferred using vildagliptin among other DPP4 inhibitors and pointed out that vildagliptin lowered HbA1c within 3 months of use.